Strategi Promosi Dalam Meningkatkan Volume Penjualan Di Showroom Nur Jaya Mobilindo Jambi - Nurdi, Deky Karya (Jurnal Dinamika Manajemen, 2020)
This study aims to determine the promotion strategy and analyze the right promotion strategy in increasing sales volume at the Nur Jaya Mobilindo Jambi showroom. Informants in this study amounted to 7 people. Data collection was carried out by interviews using interview guidelines and direct observation of the research object. This research is a descriptive research with qualitative methods. This study uses a SWOT analysis technique. The results of the study show that strategies that can be implemented by the Promotional Strategy in Increasing Sales Volume at the Nur Jaya Mobilindo Showroom include conducting continuous advertising, providing low DP, providing excellent service, participating in exhibition events, conducting periodic control of billboards, expanding advertising reach, shortening administrative processes, responding to complaining consumers quickly and increasing advertising attractiveness, shortening administrative time and always improving the company's image